Specification of complex events and their integration in the IOPT-Tools development environment - Natário, Diogo Nuno Vieira Alves (2024)
IOPT-Tools is a free online tool available at http://gres.uninova.pt/IOPT-Tools created with the aim to support the development of digital systems, offering an environment for editing, simulating and generating C and Very High-Speed Integrated Circuit Hardware Description Language (VHDL) code. This tool framework uses the Input Output Place Transition (IOPT) class of Petri nets as a graphical language, which is an extension of the Place-Transition Petri nets, as it allows the definition of input and output signals and events which makes it possible to model systems that communicate with the outside world, such as embedded digital systems and/or controllers. However, although this tool uses IOPT Petri nets with the intention of being used for modelling embedded digital systems and their controller part, it does not have an easy way to specify complex behaviours to be identified in the input signals or to be produced on output signals. This limitation forces the user to waste time and space in the model to create sub-models to detect or create the desired behaviours, which is neither practical nor effective. Therefore, this dissertation contributes to mitigate this limitation by supporting the specification of complex events and their integration in the IOPT-Tools environment, allowing their creation and definition in the model editor, their testing and validation in the simulator and their inclusion in the C and VHDL code generators. Implementing complex events in IOPT-Tools allows easier and quicker creation, defini- tion and implementation of embedded digital systems that communicate with the outside world and that need to detect specific patterns in input signals behaviours, triggering input events, and produce specific behaviours in output signals, after the occurrence of output events.